A new formula for conjugate parameter computation based on the quadratic model - Basim Abbas Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The conjugancy coefficient is the very basis of a diversity of the conjugate gradient methods. In this research, we derivation a new formula of conjugate gradient methods based on the quadratic model. Our arithmetical findings have revealed that, our new method has the most excellent performance contrast to the other standard CG methods. Also give proof viewing that this method converges globally.